A status report on AGN variability. Issue Volume 15:Issue S356(2019) (October 2019) - Lira, Paulina
Abstract: Active Galactic Nuclei (AGN) are ubiquitous variable sources. This trademark property allows the study of many aspects of AGN physics which are not possible by other means. In this review I summarize what has been learnt by the close monitoring of AGN flux variations with special emphasis in studies conducted in optical and near-infrared domain. I also highlight what knowledge is still missing from our picture of AGN phenomena, as well as possible developments expected in this new era of time-domain astronomy.